Lactobacillus strains inhibit biofilm formation of Salmonella sp. isolates from poultry - Merino, Lina Ethel (2019)
Lactic acid bacteria (LAB)exert a strong antagonistic activity against many microorganisms including food spoilage organisms and may be used as an alternative to control biofilm formation of pathogens in food industries. The objective of this work was to investigate the ability of fifteen Salmonella strains isolated from poultry environment to form biofilms on different surfaces. In addition, the effect of Lactobacillus kefiri strains 8321 and 83113 and Lactobacillus plantarum 83114 and their surface proteins on biofilm development of Salmonella Enteritidis 115 was studied. The relationship between surface properties of bacteria (hydrophobicity, autoaggregation and coaggregation with lactobacilli)and biofilm formation was also investigated. Most of Salmonella strains were hydrophilic and five strains were moderately hydrophobic. In general, Salmonella strains showed high aggregation abilities (27?54%). S. Enteritidis 106 and S. Typhimurium 102 and 108 showed the highest percentages of autoaggregation. All Salmonella strains tested showed aggregation abilities with the three lactobacilli studied, but the percentage of coaggregation proved to be strain-specific. When comparing stainless steel, glass and polystyrene surfaces, higher levels of biofilm formation occurred on polystyrene plate than on glass surfaces or stainless steel. S. Enteritidis 115 exhibited the greatest attachment to polyestyrene surface. The preincubation or coincubation with the three lactobacilli strains significantly reduced (about 1 log CFU/ml of reduction)the ability of S. Enteritidis 115 to form biofilm compared to the control without lactobacilli. These results were confirmed by confocal microscopy. In the same way, when surface proteins extracted from lactobacilli strains were preincubated or coincubated with S. Enteritidis 115, biofilm formation of this strain was significantly decreased compared to the control. The results obtained showed that these Lactobacillus strains and their surface proteins can be used as alternatives for control of biofilm formation by Salmonella in the poultry industry.